Squamous cell carcinoma of the external auditory canal with intracranial invasion - Trining Dyah; Sutji Pratiwi (PERHATI-KL, 2026)
Background: Squamous cell carcinoma (SCC) of the external auditory canal (EAC) is a rare and aggressive malignancy that may resemble chronic ear disease, causing delayed diagnosis and poor prognosis in advanced stages. Purpose: To report a case of SCC of the EAC with temporal bone and intracranial invasion. Case report: A 64-year-old male with chronic otorrhoea and previous mastoidectomy, presented with retroauricular ulcerative mass. Clinical examination found multiple ulcerative masses in the left retroauricular region. MRI showed temporal bone destruction with intracranial extension, and histopathology confirmed well-differentiated SCC, classified as stage IVA (T4N0M0). The patient underwent radical surgical excision, followed by adjuvant chemotherapy and radiotherapy; however, local recurrence occurred within six months. Clinical question: In advanced SCC of the EAC, how does multimodal therapy affect local control and outcomes? Method: A narrative evidence search was conducted through PubMed, Scopus, and Google Scholar for studies from 2016 to 2026 on SCC of the EAC, temporal bone invasion, intracranial extension, surgery, radiotherapy, chemoradiation, and multimodal therapy. Result: Evidences supported MRI for assessing tumor extension and guiding treatment. T4 disease with intracranial invasion remains associated with poor local control despite multimodal therapy. Conclusion: SCC of the EAC should be suspected in chronic otorrhea, non-healing ear lesions, or persistent symptoms after ear surgery. Early recognition, MRI-based staging, and multidisciplinary treatment are essential, although recurrence risk remains high in advanced T4 disease.